Double addition of H2 to transition metal-borane complexes: A “hydride shuttle” process between boron and transition metal centres - Tsoureas, Nikolaos; Yu-Ying, Kuo; Haddow, Mairi F.; Owen, Gareth R. (Chemical Communications, 2011)
The addition of H2 across a transition metal-borane bond is reported for the first time providing a mechanism for recharging borane functional groups to borohydride. © 2010 The Royal Society of Chemistry.